In Silico Investigation of the Anti-Tumor Mechanisms of Epigallocatechin-3-Gallate - Wang, Wang (Molecules, 2019)
The EGCG, an important component of polyphenol in green tea, is well known due to its numerous health benefits. We employed the reverse docking method for the identification of the putative targets of EGCG in the anti-tumor target protein database and these targets were further uploaded to public databases in order to understand the underlying pharmacological mechanisms and search for novel EGCG-associated targets. Similarly, the pharmacological linkage between tumor-related proteins and EGCG was manually constructed in order to provide greater insight into the molecular mechanisms through a systematic integration with applicable bioinformatics. The results indicated that the anti-tumor mechanisms of EGCG may involve 12 signaling transduction pathways and 33 vital target proteins. Moreover, we also discovered four novel putative target proteins of EGCG, including IKBKB, KRAS, WEE1 and NTRK1, which are significantly related to tumorigenesis. In conclusion, this work may provide a useful perspective that will improve our understanding of the pharmacological mechanism of EGCG and identify novel potential therapeutic targets.